Absence of Fibrinogen in Afibrinogenemia Results in Large but Loosely Packed Thrombi under Flow Conditions - Remijn, Jasper A.; Wu, Ya-Ping; IJsseldijk, Martin J. W.; Zwaginga, Jaap J.; Sixma, Jan J.; de Groot, Philip G. (Thrombosis and Haemostasis, 2001)
We studied the role of fibrinogen in platelet thrombus formation under flow on adhesive proteins using afibrinogenemic blood (LMWH anticoagulated) in a perfusion system. Perfusions with afibrinogenemic blood showed strong increased surface coverage and thrombus volume that normalized upon addition of fibrinogen. Similar studies using citrate anticoagulated blood showed that this was due to fibrinogen and not fibrin. Morphological analysis showed that afibrinogenemic thrombi were loosely packed and consisted mainly of dendritic platelets that contacted one another through filopodia. However, in the presence of fibrinogen, platelets formed lamellipodia and spread out on top of one another. Studies with radiolabeled platelets showed similar numbers of platelets in both conditions demonstrating that the difference is one of packing and the larger size is due to absence of lamellipodia formation and spreading. The found increased thrombus size and loosely packed platelets might help to understand thrombotic complications sometimes seen in afibrinogenemia patients.
Keywords: Afibrinogenemia; thrombus; flow; fibrinogen; platelet